The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1097/mph.0b013e318290c24f
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Surveillance Study of Blood Stream Infections Associated With Central Venous Access Devices (Port-type) in Children With Acute Leukemia

Abstract: The use of intensive chemotherapy and central devices has improved patients survival, but it is associated with catheter-related blood-stream infections (CRBSI). An educational program was instituted for preventing CRBSI occurrence in acute leukemia pediatric patients having totally implanted central devices. The Centers of Disease Control and Prevention criteria were used as definition for CRBSI. Data collected were age, sex, diagnosis, chemotherapy, inpatient versus outpatient, microbiological data, risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…In contrast, they noted a statistically significant increased risk for CLABSI in patients with severe neutropenia at the time of the CVC placement. 22 This is why it has been recommended that CVC placement should be avoided when ANC is <0.5 9 10 9 /L. 1 In the present retrospective study the majority of patients (95%) had a tunneled external (TE) CVC and only two patients (5%) had a totally implantable design, therefore an association between catheter design and risk for CLABSI could not be made.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…In contrast, they noted a statistically significant increased risk for CLABSI in patients with severe neutropenia at the time of the CVC placement. 22 This is why it has been recommended that CVC placement should be avoided when ANC is <0.5 9 10 9 /L. 1 In the present retrospective study the majority of patients (95%) had a tunneled external (TE) CVC and only two patients (5%) had a totally implantable design, therefore an association between catheter design and risk for CLABSI could not be made.…”
Section: Discussionmentioning
confidence: 69%
“…showed that ANC was not associated with an increased risk for developing CLABSI. In contrast, they noted a statistically significant increased risk for CLABSI in patients with severe neutropenia at the time of the CVC placement . This is why it has been recommended that CVC placement should be avoided when ANC is <0.5 × 10 9 /L …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations